437 - The elderly and their sexuality: specific challenges and the roleof the psychiatrist. (October 2021) - Pedro, Catarina; Jorge, Beatriz; Freitas, Daniela
Abstract: The model of sexuality currently in force is a young, genitalized model, that does not tolerate failures and often forgets about affective communication, sharing and body contact. This model is also not compatible with the natural aging process, generating manymyths about sexuality in later life. Although a taboo subject, the majority (up to 70%) of healthy 70-year-olds revealedthemselves to be sexually active even with some sexual dysfunction reports. Low sexual desire (up to 43%) was the most prevalent reported sexual difficulty in women, and erectiledifficulties (up to 37%) were most prevalent among men. Aging impacts sexuality in various ways: age-related organic/metabolic changes in men and women; age-related affective and cognitive changes also in both genders; age-and duration-related changes in a couple's dynamic interaction, which can lead to discrepancy between the partners and their sexual narratives. In the sexual response cycle, aging affects the stages of desire, arousal/excitement, plateau, orgasm, and resolution/refractory period both men and women. Depressed mood as well as the use of antidepressant drugs, deterioration of cognitive function and difficulties to communicate can cause loss of intimacy and emotional closeness which then may result in sexual withdrawal and difficulties. Repetitive experiences of failure increase even more the couple distress. There are also to consider medical conditions, medication side effects, loss of physical capacity, subjective loss of attractiveness, lack of a partner, institutionalization or living withtheir children, which can be obstacles to sexual activity in the elderly. Diagnostic workup has to integrate not only general medical, gynecological, urological andpsychiatric factors, but also take a systemic perspective which deals with the interaction pattern of the partners. Treatment of sexual dysfunctions in later life combines biomedical interventions with psychotherapeutic and psychosocial strategies. An essential therapeutic contribution for allcouples is, however, basic counseling and psychoeducation. Explaining how aging has an impact and how other individuals and couples experience these changes is an important step in empowering the couple, clarifying and correcting the sociocultural myths andencouraging the couple to build their very own sexuality.